THE INFLUENCE OF THE ANGLE OF SETTING THE FERTILIZER TRANSMISSION PART OF THE UNSYMMETRICAL SIDE OF THE FERTILIZER BETWEEN THE COTTON ROW ON ITS PERFORMANCE INDICATORS - Haydarova Shakhnoza Zakirjonovna; Davlitova Mohigul Mirzagani qizi (Galaxy International Interdisciplinary Research Journal, 2024)
This article provides information on the study of the influence of the setting angle of the symmetrical side of the fertilizer transfer part of the working body that applies fertilizer between cotton rows to the direction of movement on its performance. In order for the fertilization depth and soil spreading to the side to be at the level of agrotechnical requirements, and the traction resistance to be minimal, the methods of determining the angle of installation of the symmetrical side of the fertilizer transfer part of the fertilizer transfer body with respect to the direction of movement are explained.